EFEK MEDIASI GANDA DARI PERSEPSI NILAI DAN KEPUASAN PELANGGAN TERHADAP KUALITAS LAYANAN, LOYALITAS, DAN E-WOM: BUKTI DARI INDUSTRI KEDAI KOPI DI YOGYAKARTA - Khulidatiana; Retno Widowati (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
The significant growth of the coffee shop industry in Yogyakarta in recent years has created intensive competition in this sector. This emphasizes the importance of the quality of service provided in the success of the business. Although previous research has examined the relationship of perceived service quality with perceived value and customer satisfaction, there are still limited studies that integrate the mediating role of perceived value and customer satisfaction in influencing customer loyalty and electronic word-of-mouth (e-WOM) in the context of coffee shops. This study aims to analyze the complex relationships between perceived service quality, perceived value, customer satisfaction, customer loyalty and e-WOM in Fore Yogyakarta coffee shop customers. Using a quantitative approach, this study collected data from 295 consumers through a structured survey and analyzed it using Smart-PLS4 software to test the relationship between variables. The results showed that perceived service quality had a significant effect on perceived value, satisfaction, loyalty, and e-WOM. Perceived value is shown to mediate the relationship between perceived service quality and satisfaction, loyalty, and e-WOM. Similarly, customer satisfaction mediates the effect of perceived service quality on loyalty and e-WOM. These findings make a theoretical contribution to the development of consumer behavior models in the coffee shop industry by identifying the dual mediating roles of perceived value and satisfaction. Practically, the results suggest that coffee shop managers need to focus on improving service quality and customer perceived value to build loyalty and encourage positive e-WOM